2018
DOI: 10.19082/6454
|View full text |Cite
|
Sign up to set email alerts
|

Bolton discrepancy in an Iranian population and its relation with maxillary lateral incisors’ size

Abstract: BackgroundBolton’s two main ratios describing the proportional size of upper and lower teeth, could contribute to estimating the excess or deficiency of tooth size necessary to obtain an ideal occlusion. However, the mean Bolton values are not the same among different societies. Determining the prevalence of tooth size deviations from population-specific Bolton indices might help local orthodontists to have a more concise treatment plan.ObjectiveThe study aimed to define the prevalence of clinically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The ± 2SD of BM found in the current study (25%) is alike reported for other populations of the world [ Table 2 ]. [ 9 10 13 17 23 31 32 35 ] A considerable number of normal occlusion subjects (20%) in the current study had AR deviated more than ± 2SD of BM, which is significantly larger than studies on other populations [ Table 2 ]. This finding could signify the influence of ethnicity on the tooth and jaw size of an individual.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The ± 2SD of BM found in the current study (25%) is alike reported for other populations of the world [ Table 2 ]. [ 9 10 13 17 23 31 32 35 ] A considerable number of normal occlusion subjects (20%) in the current study had AR deviated more than ± 2SD of BM, which is significantly larger than studies on other populations [ Table 2 ]. This finding could signify the influence of ethnicity on the tooth and jaw size of an individual.…”
Section: Discussionmentioning
confidence: 52%
“…[ 14 ] Some studies on other ethnic groups were in concordance with Bolton's ratios,[ 11 15 16 ] while others are not. [ 17 18 ] Bolton's study was based on ideal occlusion and may not accurately contemplate the discrepancies in malocclusion cases. Some of the studies on malocclusion groups were in concordance with Bolton's ratios,[ 9 19 ] while others are not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Smith [17] also found that the overall ratio of the African Americans was larger than that of Caucasians, and this was attributed to the difference in the size of the posterior teeth. Significant differences were also seen in the anterior ratio or overall ratio compared with Bolton's original ratios among certain populations, including those from India [18], Turkey [16], Iran [19], and Saudi Arabia [42]. As early as 1991, the Chinese have established their own standard value of the Bolton ratio [43], and since then, many have studied and established standard values in different regions of China.…”
Section: Discussionmentioning
confidence: 99%
“…The Bolton analysis is now commonly used by clinicians as an objective method for the precise measurement of tooth proportion to guide clinical diagnosis and treatment. This has been studied across different ethnicities and regions [15][16][17][18][19], among various types of malocclusion [20][21][22][23][24], and in the presence of new indicators [25]. These studies did improve the accuracy and applicability of the Bolton analysis.…”
Section: Introductionmentioning
confidence: 99%